A Survey of Task Allocation and Load Balancing in Distributed Systems - Jiang, Yichuan (IEEE transactions on parallel and distributed systems, 2016)
In past decades, significant attention has been devoted to the task allocation and load balancing in distributed systems. Although there have been some related surveys about this subject, each of which only made a very preliminary review on the state of art of one single type of distributed systems. To correlate the studies in varying types of distributed systems and make a comprehensive taxonomy on them, this survey mainly categorizes and reviews the representative studies on task allocation and load balancing according to the general characteristics of varying distributed systems. First, this survey summarizes the general characteristics of distributed systems. Based on these general characteristics, this survey reviews the studies on task allocation and load balancing with respect to the following aspects: 1) typical control models; 2) typical resource optimization methods; 3) typical methods for achieving reliability; 4) typical coordination mechanisms among heterogeneous nodes; and 5) typical models considering network structures. For each aspect, we summarize the existing studies and discuss the future research directions. Through the survey, the related studies in this area can be well understood based on how they can satisfy the general characteristics of distributed systems.